Influence of fibre design and curvature on crosstalk in multi-core fibre. (29th March 2016) - Egorova, O N; Astapovich, M S; Melnikov, L A; Salganskii, M Yu; Mishkin, S N; Nishchev, K N; Semjonov, S L; Dianov, E M
Abstract: We have studied the influence of cross-sectional structure and bends on optical cross-talk in a multicore fibre. A reduced refractive index layer produced between the cores of such fibre with a small centre-to-centre spacing between neighbouring cores (27 μm) reduces optical cross-talk by 20 dB. The cross-talk level achieved, 30 dB per kilometre of the length of the multicore fibre, is acceptable for a number of applications where relatively small lengths of fibre are needed. Moreover, a significant decrease in optical cross-talk has been ensured by reducing the winding diameter of multicore fibres with identical cores.